Identification of the gut microbiota affecting Salmonella pullorum and their relationship with reproductive performance in hens - Niu, Qing; Wang, Xiaoxu; Qi, Xinyong; Cao, Changjian; Yang, Kaixuan; Gu, Caiju; Zhou, Zhenxiang; Huang, Qizhong (Frontiers in Microbiology, 2023)
Introduction Pullorum disease is one of the common bacterial infectious diseases caused by Salmonella pullorum (S. pullorum), which can result in a decrease in the reproductive performance of laying hens, thus causing considerable economic losses. However, studies about the characteristics of intestinal microbiota with pullorum and their potential association with reproductive performance in hens are still limited. This study was to identify the gut microbiota associated with S. pullorum in poultry. Methods A total of 30 hens with S. pullorum-negative (PN) and 30 hens with S. pullorum-positive (PP) were analyzed for hatching eggs laid in 2 weeks (HEL), fertilization eggs (FE), chick number (CN), and microbial structure. Results There were significant differences in HEL (p < 0.01), FE (p < 0.01), and CN (p < 0.01) between PP and PN. Histomorphological observations showed abnormal morphology of the ovaries and fallopian tubes and low integrity of epithelial tissue in the ileum and cecum in PP. 16S rRNA gene sequencing revealed that beneficial cecal microbes, such as Bacteroides, Desulfovibrio, and Megamonas, were positively correlated with reproductive performance and had lower abundance in PP (p = 0.001). Furthermore, diminished phosphotransferase system (PTS) and pentose phosphate pathway, butanoate metabolism and oxidative phosphorylation were also found in PP. Discussion Taken together, this study clarified the morphological characteristics of the reproductive tract and intestines of chickens infected with S. pullorum and preliminarily explored the potential association between cecal microbiota and reproductive performance in hens. Our data may provide a reference for revealing the intestinal microbial characteristics of hens in resisting pullorum and exploring novel approaches to infection control in future studies.